2019
DOI: 10.1093/annonc/mdz285
|View full text |Cite
|
Sign up to set email alerts
|

Development of adaptive immune effector therapies in solid tumors

Abstract: State-of-the-art treatment strategies have drastically ameliorated the outcome of patients affected by cancer. However, resistant and recurrent solid tumors are generally nonresponsive to conventional therapies. A central factor in the sequence of events that lead to cancer is an alteration in antitumor immune surveillance, which results in failure to recognize and eliminate the transformed tumor cell. A greater understanding of the dysregulation and evasion of the immune system in the evolution and progressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 117 publications
(144 reference statements)
0
29
0
Order By: Relevance
“…24 The use of SD-208 to block TGF-β-receptor signaling is also compatible with CAR T-cell products that target alternative antigens in TNBC, for example, mesothelin, B7-H3 and GD2, and may be combined with other strategies such as immune checkpoint blockade that are currently being investigated to augment the potency of CAR T-cell therapy. 25 Further, TGF-β-receptor signaling blockade may be applied to augment CAR T-cell potency in other cancer entities that have been demonstrated to produce TGF-β, eg pancreatic, esophageal, stomach, colon and prostate cancers. 26 Open access…”
Section: Open Accessmentioning
confidence: 99%
“…24 The use of SD-208 to block TGF-β-receptor signaling is also compatible with CAR T-cell products that target alternative antigens in TNBC, for example, mesothelin, B7-H3 and GD2, and may be combined with other strategies such as immune checkpoint blockade that are currently being investigated to augment the potency of CAR T-cell therapy. 25 Further, TGF-β-receptor signaling blockade may be applied to augment CAR T-cell potency in other cancer entities that have been demonstrated to produce TGF-β, eg pancreatic, esophageal, stomach, colon and prostate cancers. 26 Open access…”
Section: Open Accessmentioning
confidence: 99%
“…However, some promising results have also been reported in some early phase studies [91]. Phase 1 studies of GD2-specific CAR-T cells for neuroblastoma, CAR-T cells specifically targeting HER2, EGFR and IL-13 for glioblastoma multiforme, mesothelin-specific CAR-T cells for advanced malignant pleural mesothelioma or pancreatic cancer, CAR-T cells specific for epidermal growth factor receptor (EGFR) for advanced nonsmallcell lung cancer and cholangiocarcinoma, CEA specific CAR-T cells for metastatic CRC have reported positive initial results [92][93][94][95][96][97][98][99].…”
Section: Chimeric Antigen Receptort-cell (Car-t) Therapy For Solid Tumentioning
confidence: 98%
“…The infiltration of the tumor tissue with T cells targeting tumor associated antigens has been shown to be associated with a favorable prognosis in several solid tumors. Upon this observation ongoing studies have been investigating the idea of extraction, ex vivo expansion with homeostatic cytokines and reinfusion into the patients as a novel treatment strategy [91]. Tumor infiltrating lymphocytes (TILs) were first reported by Rosenberg et al in 1988 and they demonstrated the antimelanoma effects of IL-2 induced TILs [100].…”
Section: Tumor Infiltrating T-cells In Refractory Solid Tumorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Keeping in mind the crucial role of preserved renal function, it is logical that renal dysfunction/involvement automatically upgrades the risk category. Therapy-Related Factors During the last twenty years, particularly the last decade, the expanding knowledge of cancer immune evasion mechanisms and host-tumor interactions has significantly changed our therapeutic strategies in hemato-oncology [21][22][23][24][25]. Several novel targeted molecular and immune cell-based agents are now available, usually to be used in combination with conventional cytotoxic agents [26].…”
Section: Cancer-related Factorsmentioning
confidence: 99%